Immunohistochemical Expression of PCNA and Ki-67 in Periapical Granuloma and Radicular Cyst - Sargolzaei, Soudabeh; Roufegarinejad, Arezoo; Shamszadeh, Sayna (Journal of Dental School, 2019)
Objectives: Periapical Granulomas (PGs) and Radicular Cysts (RCs), as the most common odontogenic lesions have yet unclear pathogenesis. This study was aimed to compare PCNA and Ki-67 expression in PGs and RCs and evaluate their possible relationship with two lesions. Methods: In this cross-sectional descriptive study, twenty PGs and twenty RCs were evaluated immunohistochemically using an anti-PCNA and anti-Ki-67 polyclonal antibodies. PCNA+ and Ki-67+ cells were counted in connective tissue wall and epithelial lining (in RCs). Statistical analysis was performed by using Mann-Whitney U test and Spearman’s rank correlation coefficient. Results: In PGs, percentage of PCNA and Ki-67 expression were found 70% and 30%, respectively; In RCs, PCNA and Ki-67 expression were observed 90% and 55%, respectively. Additionally, in RCS, Immunoexpression of PCNA (85%) and Ki-67 (60%) were detected at epithelial lining area. The positive immunoexpression of PCNA in RCs was greater than PGs (p<0.05). Conclusion: Immunoexpression of PCNA and Ki-67 were detected in both lesions which may be mentioned as valuable markers for the prediction of biologic behavior of PGs and RCs.